Question and Answers Forum

All Questions      Topic List

Others Questions

Previous in All Question      Next in All Question      

Previous in Others      Next in Others      

Question Number 64872 by Rio Michael last updated on 22/Jul/19

Given that    y = (cosx^ )^(sinx)   find (dy/dx)  and     lim_(x→0)  y

$${Given}\:{that}\: \\ $$$$\:{y}\:=\:\left({cosx}^{} \right)^{{sinx}} \:\:{find}\:\frac{{dy}}{{dx}} \\ $$$${and}\: \\ $$$$\:\:\underset{{x}\rightarrow\mathrm{0}} {{lim}}\:{y} \\ $$

Commented by kaivan.ahmadi last updated on 22/Jul/19

lny=sinxln(cosx)⇒((y′)/y)=cosxln(cosx)−((sinx)/(cosx))sinx⇒  (dy/dx)=(cosx)^(sinx) (cosxln(cosx)−((sin^2 x)/(cosx)))    lim_(x→0) cosx^(sinx) =1^0 =1

$${lny}={sinxln}\left({cosx}\right)\Rightarrow\frac{{y}'}{{y}}={cosxln}\left({cosx}\right)−\frac{{sinx}}{{cosx}}{sinx}\Rightarrow \\ $$$$\frac{{dy}}{{dx}}=\left({cosx}\right)^{{sinx}} \left({cosxln}\left({cosx}\right)−\frac{{sin}^{\mathrm{2}} {x}}{{cosx}}\right) \\ $$$$ \\ $$$${lim}_{{x}\rightarrow\mathrm{0}} {cosx}^{{sinx}} =\mathrm{1}^{\mathrm{0}} =\mathrm{1} \\ $$

Commented by mathmax by abdo last updated on 22/Jul/19

we have y =e^(sinxln(cosx))  ⇒(dy/dx) =(d/dx)( sinx ln(cosx))e^(sinxln(cosx))   ={cosxln(cosx) +sinx ((−sinx)/(cosx))}y(x) ⇒  y^′ (x)=((cos^2 x ln(cosx)−sin^2 x)/(cosx))× (cosx)^(sinx)

$${we}\:{have}\:{y}\:={e}^{{sinxln}\left({cosx}\right)} \:\Rightarrow\frac{{dy}}{{dx}}\:=\frac{{d}}{{dx}}\left(\:{sinx}\:{ln}\left({cosx}\right)\right){e}^{{sinxln}\left({cosx}\right)} \\ $$$$=\left\{{cosxln}\left({cosx}\right)\:+{sinx}\:\frac{−{sinx}}{{cosx}}\right\}{y}\left({x}\right)\:\Rightarrow \\ $$$${y}^{'} \left({x}\right)=\frac{{cos}^{\mathrm{2}} {x}\:{ln}\left({cosx}\right)−{sin}^{\mathrm{2}} {x}}{{cosx}}×\:\left({cosx}\right)^{{sinx}} \\ $$

Commented by mathmax by abdo last updated on 22/Jul/19

we have y(x) =e^(sinxln(cosx))     and lim_(x→0) sinxln(cosx) =0 ⇒  lim_(x→0)  y(x) =1

$${we}\:{have}\:{y}\left({x}\right)\:={e}^{{sinxln}\left({cosx}\right)} \:\:\:\:{and}\:{lim}_{{x}\rightarrow\mathrm{0}} {sinxln}\left({cosx}\right)\:=\mathrm{0}\:\Rightarrow \\ $$$${lim}_{{x}\rightarrow\mathrm{0}} \:{y}\left({x}\right)\:=\mathrm{1} \\ $$

Commented by Masumsiddiqui399@gmail.com last updated on 23/Jul/19

K

Terms of Service

Privacy Policy

Contact: info@tinkutara.com